2013
DOI: 10.2527/jas.2011-4999
|View full text |Cite
|
Sign up to set email alerts
|

Rumen morphometrics and the effect of digesta pH and volume on volatile fatty acid absorption1

Abstract: The effects of rumen digesta volume and pH on VFA absorption and its relation to rumen wall morphology were evaluated. Nine rumen cannulated cows formed 3 groups based on desired variation in rumen morphology: The High group was formed by Holsteins yielding 25.9 kg milk/d and fed on a high-grain total mixed ration (TMR); the Medium group by Holstein-Zebu crossbreds yielding 12.3 kg milk/d and fed on corn silage, tropical pasture, and a commercial concentrate; and the Dry group by nonlactating grazing Jerseys f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 18 publications
2
45
0
1
Order By: Relevance
“…As reported by Resende Júnior, et al (2006b), the inaccuracies in the macroscopic measurement technique may decrease accurate detection of behavior differences in the extension of the rumen's absorptive surface. However, other authors have reported accurate measurements of the extent of the absorptive surface using the same technique described in the current experiment (Melo et al, 2013).…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…As reported by Resende Júnior, et al (2006b), the inaccuracies in the macroscopic measurement technique may decrease accurate detection of behavior differences in the extension of the rumen's absorptive surface. However, other authors have reported accurate measurements of the extent of the absorptive surface using the same technique described in the current experiment (Melo et al, 2013).…”
Section: Resultsmentioning
confidence: 61%
“…This finding is in contrast to reports of animals in early lactation, likely because the animals in this study had a lower metabolic demand, as they were neither pregnant nor lactating. While the ruminal epithelium is known to respond positively to introduction of high-energy diets (Dirksen et al, 1984;Melo et al, 2013), the response of the omasal epithelium to high-energy diets has not been evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation for the effect of the transitional diet on post-partum DMIBW could be the adaptation of the rumen epithelium (Melo et al, 2013;Teófilo et al, 2011;Dirksen et al, 1984). This adaptation could have induced higher synchrony between the production and removal of VFAs in the reticulorumen, which enables greater equilibrium in the rumen environment, with a pH that is more stable and closer to normality.…”
Section: Resultsmentioning
confidence: 99%
“…Although studies that measured the height and area of the omasum papillae were not found in the literature, it is widely known that the area and height of the rumen papillae respond positively to a high calorie diet, inducing a larger absorptive surface for VFAs (Melo et al, 2013;Teófilo et al, 2011;Dirksen et al, 1984;Beharka, 1998;Shen et al, 2004). One week before parturition and two weeks postpartum, the height of the omasum papillae tended to be higher when the cows were fed the HGC diet (Figure 5), in which less abrasiveness was expected.…”
mentioning
confidence: 99%